The Theory of Dhikr Perspective of Abdurrauf As-Singkili (An Analysis of Therapeutic Approaches to Promoting Mental Health): Teori Dzikir dari Perspektif Abdurrauf As-Singkili (Analisis Pendekatan Terapi untuk Meningkatkan Kesehatan Mental) - Rizki Melanie; Jarman Arroisi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The development of knowledge on mental health indicates that psychological and spiritual factors are closely interconnected in shaping an individual’s balance. This article aims to analyze Abdurrauf As-Singkili’s perspective on dhikr and its relationship to the enhancement of mental health in modern society. The methodology employed in this study is a literature review that examines Abdurrauf As-Singkili’s major works, particularly those related to tazkiyat al-nafs, dhikr, and suluk, as well as explores modern literature concerning psychosomatic issues and mental health. The findings reveal that dhikr plays a significant therapeutic role, serving as a means of emotional stabilization, strengthening spiritual awareness, and developing psychological resilience. The regular practice of dhikr can reduce anxiety, manage stress, and foster inner tranquility through the mechanisms of hudhur al-qalb (presence of the heart) and muraqabah (spiritual awareness). These findings highlight that the integration of spiritual values, particularly through dhikr, can serve as a comprehensive approach to addressing mental health problems. Therefore, the understanding of dhikr according to Abdurrauf As-Singkili is relevant as a supportive model of spiritual therapy for contemporary society.